Synthesis of diacetyl gamavuton-0 using acetyl chloride as an acylating agent - Margono, Supardjan Amir; Zendrato, Ridho Nugroho (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2006)
Gamavuton-0 (GVT-0) is a curcumin-like compound, which is more stable than curcumin and still has an antioxidant property. The synthesis of diacetyl gamavuton-0 (diAcGVT-0) yielding an acetylation product that is more lipophile than GVT-0. The synthesis of diAcGVT-0 has been done by reacting GVT-0 and acetyl chloride as an acylating agent and tertiary amines as primary bases. DiAcGVT-0 was formed as the major product of synthesis but the product was not pure. Structure elucidation using UV-Vis, IR, 1H NMR and MS spectra showed that the main product was diAcGVT-0.Key words : diacetyl gamavuton-0, acetyl chloride, acylating agent, lipophile